PENGARUH MOTIVASI KERJA DAN DISIPLIN KERJA TERHADAP KEPUASAN KERJA KARYAWAN - Wiratmaja, Azi Pangestu; Hawignyo, Hawignyo (Program Studi Pendidikan Manajemen Perkantoran, 2021)
Facing competition and change at both the international and national levels, employees must therefore adapt to changes in technology, such as the emergence of new technology or new work methods in the company. The method used in this research is quantitative method. This study uses multiple linear regression analysis. The sampling technique used slovin. The data used in this study are premiere data sourced from PT. Nichias Rockwool Indonesia. The results of research partially on employee job satisfaction shows 3,833 1,976 t table is greater, it means that partially there is an effect of work motivation on employee job satisfaction 21.976 tcount is greater than table value, meaning that partially there is an influence of work motivation on job satisfaction. Simultaneous results show that the value of Fcount with Ftable is 748.631 3.06, the value of Fcount is greater than the value of Ftable, which means that there is a simultaneous influence of work motivation and work discipline on job satisfaction.Keyword : Regresion, Motivation, Dicipline, Employee Satisfaction